The Role of Leadership in Improving the Quality of Healthcare Services at Community Health Centers : A Systematic Review - Emma Puspita Kartikasari; Arih Diyaning Intiasari; Budi Aji (Eduvest - Journal of Universal Studies, 2024)
Various factors related to the quality of health services in primary health care facilities include health care providers, organizational and leadership factors, and environmental factors (internal and external). A leadership role is required, especially in terms of company-wide coordination and of course motivation. This study used a systematic review method. Electro databases used included Google Scholar, Pubmed, & Garuda Journal using the key terms "leadership role", "health service quality", & "puskesmas". Based on the results of the research conducted, it was found that the role of leadership has an impact on improving the quality of health services at the puskesmas. The role of a leader in an organization is very important. This is because the leader is one of the gates or spearheads that is very important in planning the success of an organization. To increase employee creativity and innovation to achieve organizational goals, the manager's role is to encourage employees to express their creativity and recognize the results of their efforts.